Rancang Bangun Sistem IT-Helpdesk Untuk Maintenance dan Tutorial Aplikasi Simplebiz Menggunakan Metode Forward Chaining dan Certainty Factor - Wira Partha, I Gusti Ngurah; Hartati, Rukmi Sari; Jasa, Lie (Majalah Ilmiah Teknologi Elektro; Vol 20 No 2 (2021): (Juli-Desember) Majalah Ilmiah Teknologi Elektro, 2021)
Simplebiz application is a general term for 20 desktop-based business applications that have been built and developed by PT. Bamboomedia Cipta Persada. Until now, the number of users of the simplebiz application throughout Indonesia has reached 10,508 people, while the number of technical support in the IT-helpdesk division at PT. Bamboomedia Cipta Persada only 2 people. Based on these problems, it is necessary to have a system that can be used by users of the simplebiz application to obtain solutions to the problems they face, as if they were consulting directly with a technical support, so that it is expected to be able to help technical support in the IT-helpdesk division at PT. Bamboomedia Cipta Persada in handling and reducing the number of complaints received either face-to-face, by telephone, or via SMS. In this research, an IT-helpdesk system for maintenance and simplebiz application tutorial has been successfully designed and built using forward chaining and certainty factor Methods. The percentage of confidence from the solution generated by the system to the problems faced by simplebiz application users is 80% and the level of confidence from the output to the contribution of solving the problem is ALMOST SURE.